Brittleness evaluation of the inter-salt shale oil reservoir in Jianghan Basin in China. (April 2019) - Fan, X.; Su, J.Z.; Chang, X.; Huang, Z.W.; Zhou, T.; Guo, Y.T.; Wu, S.Q.
Abstract: The inter-salt shale in the Qianjiang formation of Jianghan Basin in China are characterized by multiple bedding planes, low rock strength, complicated mineral compositions and high heterogeneity of rock mechanics. The brittleness evaluation of the inter-salt shale has not been investigated. Core samples of the inter-salt shale from the fourth member of the Qianjiang Formation were tested by using CT scan, X-ray diffraction, tri-axial rock test at the in-situ condition. An integrated investigation was conducted on the brittleness evaluation of inter-salt shale from the perspective of core characteristics, brittle mineral components, elastic parameters and the complete stress–strain characteristics of rocks. The results indicate that the inter-salt shale exist with bedding planes and glauberite, which leads to high anisotropy and heterogeneity. The argillaceous dolomite is a good candidate for fracturing due to high brittle mineral content. The elastic parameters of the inter-salt shale at the in-situ conditions are quite different with that of the gas shale because of the difference in the mineral composition, the bedding plane structure and the fluid type stored in the pore space. The brittleness index of the inter-salt shale can be calculated through a modified Rickman model. The transformation model of the dynamic-static mechanic parameters has been built based on the logging data and the laboratory data in order to obtain the brittleness index profile along the wellbore. The post-peak stress-strain relations indicates the rock has high residual strength at confined stress state, which explains that the rock is damaged through shear failure along the bedding plane and fails to generate complex fractures. This study would provide theoretical basis for fracability evaluation model used in the inter-salt shale oil reservoir. Highlights: The elastic parameters of the inter-salt oil shale are quite different with that of the gas shale. The mechanical brittleness index profile along the wellbore of the shale oil reservoir can be obtained. The inter-salt oil shale is semi-brittle at the high level of confining pressure based on the full stress-strain curve theory.